The Role of Decompressive Craniectomy in Limited Resource Environments - Clavijo, Angélica; Khan, Ahsan A.; Mendoza, Juliana; Montenegro, Jorge H.; Johnson, Erica D.; Adeleye, Amos O.; Rubiano, Andrés M. (Frontiers in Neurology, 2019)
Decompressive craniectomy (DC) is a neurosurgical procedure useful to prevent and manage the impact of high intracranial pressure (ICP) that leads to brain herniation and brain´s tissue ischemia. In well-resourced environment this procedure has been proposed as a last tier therapy when ICP is not controlled by medical therapies in the management of different neurosurgical emergencies like traumatic brain injury (TBI), stroke, infectious diseases, hydrocephalus, tumors, etc. The purpose of this narrative review is to discuss the role of DC in areas of low neurosurgical and neurocritical care resources. We performed a literature review with a specific search strategy in web repositories and some local and regional journals from Low and Middle-Income Countries (LMICs). The most common publications include case reports, case series and observational studies describing the benefits of the procedure on different pathologies but with several types of biases due to the absence of robust studies or clinical registries analysis in these kinds of environments.